Screening Tools Designed to Assess and Evaluate Oropharyngeal Dysphagia in Adult Patients: A Scoping Review - Rafael A. Bernardes; Arménio Cruz; Hugo Neves; Vítor Parola; Nuno Catela (MDPI AG, 2022)
Oropharyngeal Dysphagia (OD) significantly decreases a patient's quality of life and poses a high economic burden to institutions. In this sense, evaluation and assessment are important interventions for health professionals, although current tools and instruments are multiple and are dispersed in the literature. The aim of this review was to map existing screening tools to assess and evaluate OD in adult patients, identify their relevant clinical parameters and respective contexts of use and provide a systematic approach and summary to better inform practice. A scoping review was developed guided by the JBI methodology and using PRISMA-ScR to report results published between 2014 and 2021, in English, Spanish and Portuguese. Databases included Medline, Academic Search Complete, CINAHL Complete, Scielo, Google Scholar, ScienceDirect, OpenGrey and B-On. Mendeley was used to store and screen data. A total of 33 studies were included in the study, of which 19 tools were identified, some being intervention-based tools and others an algorithm for decision. The most common context used was in the general population and older adults. Regarding clinical parameters, the most common were food consistency, presence of the cough reflex, swallowing effort, voice changes and weight. As oropharyngeal dysphagia concerns important risks for the patient, a rigorous assessment must be performed. In this sense, the review identified specific disease-related tools and more general instruments, and it is an important contribution to more efficient dysphagia screening and prevention.